In vitro antioxidant, a-amylase and a- glucosidase inhibitory activity of bark of erythropalum scandens blume. - Tharu, Ram Jeevan (2021)
ABSTRACT: A category of metabolic diseases characterized over and extended period by high blood sugar level is Diabetes mellitus (DM), generally referred to as diabetes, Some plant species contain active chemical constituents responsible for a- amylase and a-glucosidase inhibition and can also be used as therapeutic. This research focuses primarily on the inhibition of a- amylase and a-glucosidase by screening methanolic extracts of bark E. scandens, which are indicated as having anti-diabetic properties based on ethnobotanical value. Phytochemical screening of methanolic extract of bark of E. scanens was done and it showed the presence of alkaloids, phenolics, steroids, glycosides, terpenoids. Total phenolic content and flavonoid content in methanolic extract of bark of E. scandens was found to be 179.43+- 3.40mg GAE/gm, and 10.62+- 0.34mg QE/gm respectively. Similarly, among extracts of four fractions, the methanolic extract showed the highest antioxidant activity with and IC50valeue of 59.35+- 5.47 ug/mL. E. scandens bark showed potent a-amylase and a-glucosidase inhibition and was subjected to solvent fractionation. The methanolic extract of E. scandens showed maximum inhibition to a-amylase and a-glucosidase with IC50 values of 45.24 +- 0.89ug/mL and 35.45 +- 0.69 ug/mL, respectively. Similarly, the ethyl acetate fraction of E. scandens showed inhibition towards a-amylase and a-glucosidase compared toother fractions with IC50 values of 44.51 +- 0.12 and 17.92 +- 0.88 ug/mL, respectively. Moreover, The plant was found active against Gram-positive Staphylococcus aureus with zone of inhibition (ZOI) of 18mm. The MIC and MBC were determined by the Resazurin Microtiter Assay(REMA) method and found to be 1.562 mg/mL and 6.25 mg/mL, respectively. Compunds were isolated from ethyl acetate fractions where IR spectra of the comound showed presence of carbonyl compound and elucidation of structure yet to be done. Keywords: Sikari Lahara, Diabetes, MIC, MBC, Erythropalum scandens Blum.